THE EFFECT OF PROFITABILITY, LIQUIDITY, AND SOLVENCY ON STOCK PRICES ON THE INDONESIA STOCK EXCHANGE WITH DIVIDEND POLICY AS A MODERATING VARIABLE (A CASE STUDY OF COMPANIES IN THE HEALTHCARE SECTOR) - Andriani, Bella Delvia; Kusuma, Poppy Dian Indira; Farida, Yusriati Nur (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
The research aims to determine whether there is an effect of profitability, liquidity, and solvency on stock prices in health sector companies listed on the Indonesia Stock Exchange in 2019-2023 and to determine whether dividend policy as a moderating variable is able to strengthen the influence between the dependent variable and the independent variable. The population in this research were healthcare sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023, with a total population of 33 companies. The sampling technique used in this research was purposive sampling, resulting in 9 healthcare sector companies that met the sample criteria. The results of this research indicate that: (1) Profitability has a negative effect on stock prices, (2) Liquidity has a positive effect on stock prices, (3) Solvency has a negative effect on stock prices, (4) Dividend policy does not strengthen the effect of profitability on stock prices, (5) Dividend policy strengthens the effect of liquidity on stock prices, (6) Dividend policy does not moderate the effect of solvency on stock prices.